Declines in TBT contamination in Irish coastal waters 1987–2011, using the dogwhelk (Nucella lapillus) as a biological indicator. Issue 1 (15th November 2015) - Wilson, J.G.; Minchin, D.; McHugh, B.; McGovern, E.; Tanner, C.J.; Giltrap, M.
Abstract: Using the vas deferens sequence index (VDSI) and relative penis size index (RPSI) in dogwhelks ( Nucella lapillus ), imposex levels were assessed at 63 sites within 11 sea inlets during 2010/2011 and compared these with levels gathered since 1987. Sterile females (VDS > 5.0) were found at 14 of the 63 sites and 47 sites (75%) met the EcoQO (VDSI < 2.0). The absence of imposex in 'control' areas on the west coast is due to the lack of vessel paint applications or net dips with TBT being used as an active anti-fouling ingredient. A significant decline was observed following 2005 when comparing VDSI levels which is consistent with the decline of TBT usage. Current levels are consistent with an overall improvement towards achieving Good Environmental Status according to the requirements under the Marine Strategy Framework Directive. Highlights: Imposex values in Nucella lapillus over three decades at multiple locations around Ireland A reduction in imposex levels was observed since 2005. There was no significant correlation between VDSI and RPSI. Sterile female gastropods still present at some locations around Ireland Imposex values are consistent with achieving Good Environmental Status.